The Influence of Molecular Structure on Odor Qualities and Odor Detection Thresholds of Volatile Alkylated Phenols - Martin Czerny; R. BRUECKNER; Erhard Kirchhoff; R. Schmitt; Andrea Buettner (2011)
The relationship between chemical structure and odor characteristics of aroma compounds is interesting in terms of establishing a fundamental understanding and, in the long term, a perspective for the prediction of odor qualities and intensities of unknown compounds; on the other hand, such studies provide a useful tool to analytically elucidate compounds that are exceptionally potent odor contributors to a specific smell. In this respect, a broad knowledge of compounds with regard to their odor threshold and smell specificities compiled in a comprehensive odor library would drastically simplify the chemoanalytical process in identifying aromas and smells. Whereas numerous odor-active substance classes have been investigated intensively, such relationships and fundamental data have hitherto not been established for volatile phenols. In this study, a homologous series and isomers of 30 volatile phenols, including monoalkylated phenols and di- and trimethylphenols, were evaluated by determining their aroma attributes and their odor detection thresholds in air. The investigation demonstrates that the odor qualities, among them leather-like, horse stable-like, and medicinal, as well as the respective threshold values clearly depend on the arrangement of the alkyl substituents at the phenol ring. In particular, phenols with monoalkyl groups in the meta-position were found with very low odor detection thresholds of <1 ng/L air. A comparison of some selected phenols and their corresponding toluenes, which were found to be almost odorless, showed in addition that the phenolic hydroxyl group is obviously an important factor for the odor characteristic of this substance class.